BMAA-protein interactions: A possible new mechanism of toxicity. (1st March 2018) - van Onselen, R.; Downing, T.G.
Abstract: β- N -methylamino-L-alanine (BMAA) has been shown to accumulate in organisms by associating with host proteins. It has been proposed that this association is the result of misincorporation of BMAA into the primary structure of proteins, specifically in the place of L-serine, and that this misincorporation causes protein misfolding resulting in the tangle formation typically associated with neurodegenerative diseases. However, more recent studies have questioned the validity of the BMAA misincorporation hypothesis. Furthermore, BMAA association with proteins in the absence of de novo protein synthesis has been demonstrated although the nature of these associations has not yet been characterized. We therefore sought to investigate the effects of these undescribed interactions on protein functioning, and to identify the site(s) of these interactions. We present data here to show that BMAA can inhibit the activity of certain enzymes, interfere with protein folding in the absence of de novo protein synthesis, and associate in vitro with commercial proteins to such an extent that it cannot be removed by protein precipitation or denaturation. Based on the observed effects of these interactions on protein functioning, we suggest that this might constitute an additional mechanism of toxicity that could help to explain the role of BMAA in the development of neurodegenerative diseases. Highlights: BMAA binds strongly to proteins. BMAA cannot be removed from proteins by TCA precipitation, or denaturation with SDS or DTT. BMAA inhibits enzymes with functional hydroxyls in their active sites. BMAA interferes with the proper folding of proteins.